2019
DOI: 10.3390/nu11102509
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Health Benefits of Snap Bean: Genome-Wide Association Studies of Total Phenolic Content

Abstract: Snap beans are a significant source of micronutrients in the human diet. Among the micronutrients present in snap beans are phenolic compounds with known beneficial effects on human health, potentially via their metabolism by the gut-associated microbiome. The genetic pathways leading to the production of phenolics in snap bean pods remain uncertain. In this study, we quantified the level of total phenolic content (TPC) in the Bean Coordinated Agriculture Program (CAP) snap bean diversity panel of 149 accessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 76 publications
1
38
0
2
Order By: Relevance
“…The bean grain is constituted by three tissues: cotyledons (89%), the seed coat (10%), and the embryo (1%) (Chávez‐Mendoza & Sánchez, 2017; Morales‐Santos et al., 2017). The localization of phenolics in beans is related to genetic factors, the seed coat being the structure with the highest content, acting as a protection for cotyledons that differ in their phenolic content (Myers et al., 2019; Singh et al., 2017). Anthocyanins, condensed tannins, kaempferol glucoside, and quercetin are the main phenolic compounds of the seed coat, whereas phenolic acids like ferulic, synaptic, chlorogenic, and other hydroxycinnamic acids, are found mainly in the cotyledon (Chávez‐Mendoza & Sánchez, 2017; Nurzyńska‐Wierdak et al., 2019; Quiróz‐Sodi et al., 2018).…”
Section: Phenolic Compounds: Bioactive Compounds In Beansmentioning
confidence: 99%
“…The bean grain is constituted by three tissues: cotyledons (89%), the seed coat (10%), and the embryo (1%) (Chávez‐Mendoza & Sánchez, 2017; Morales‐Santos et al., 2017). The localization of phenolics in beans is related to genetic factors, the seed coat being the structure with the highest content, acting as a protection for cotyledons that differ in their phenolic content (Myers et al., 2019; Singh et al., 2017). Anthocyanins, condensed tannins, kaempferol glucoside, and quercetin are the main phenolic compounds of the seed coat, whereas phenolic acids like ferulic, synaptic, chlorogenic, and other hydroxycinnamic acids, are found mainly in the cotyledon (Chávez‐Mendoza & Sánchez, 2017; Nurzyńska‐Wierdak et al., 2019; Quiróz‐Sodi et al., 2018).…”
Section: Phenolic Compounds: Bioactive Compounds In Beansmentioning
confidence: 99%
“…Genomic positions for 96 previously reported QTL [10,12,14,15,19] for pod morphological traits in common bean were examined for overlap with the QTL identi ed in this work ( Figure 2). There were 15 genomic regions where a reported QTL and QTL detected in this study for pod traits overlapped (Table 3; Figure 2).…”
Section: Co-location Of Qtlmentioning
confidence: 99%
“…For QTL alignments, published mapping data from four independent studies that reported QTL for pod morphological traits in common bean [10,12,13,14,15,19] were considered. Physical position was used to investigate the correspondence between the genomic regions identi ed in this work with the previously reported QTL.…”
Section: Qtl Alignmentmentioning
confidence: 99%
“…Two papers describe the potential health-related traits of two common bean market classes, i.e., mung bean [17] and lupin bean [23]. The genetic basis for variation among snap beans, the edible immature stage of common bean, that regulates the content of phenolic compounds is also reported [21]. Of the other 12 pulse-related papers published by Nutrients but not included in this Special Issue, none were placed in this domain.…”
Section: Domain: Germplasm Resourcesmentioning
confidence: 99%
“…Eight of these papers are collected in this Special Issue. In order to guide the reader interested in the topic of pulses and human health, the references to all 20 papers are provided [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. These publications can be grouped into three primary domains that are judged to be critical to understanding the multi-dimensional framework underlying pulse consumption and human health.…”
mentioning
confidence: 99%